Autentyczna komunikacja w dyskursie edukacyjnym: rola języka nauczanego i ojczystego - Niżegorodcew, Anna (Neofilolog, 2012)
This article discusses different approaches to authentic communication, pro-posing a new definition of authentic communication in educational discourse, based on this author’ s application of Sperber and Wilson’s (1986/1995) Relevance Theory to functions of target and native language in the lan-guage classroom. According to the proposed definition, authentic com-munication in the L2 classroom refers to such uses of teachers and stu-dents’ communication which provides students both with linguistic data (positive input) and facilitates the learning process by explicitly focusing their attention on linguistic forms (negative input). After outlining some fundamental principles of Relevance Theory, the author exemplifies func-tions of the target language (English) and the mother tongue (Polish) in authentic communication in educational discourse in three stages of L2 lessons: in explicit grammar teaching, in fluency practice and in real class-room communication. Although it is claimed that the mother tongue should be preserved in monolingual teaching contexts, primarily for iden-tification and affective reasons, excessive use of the native language re-duces the target language to the function of a teaching object and, conse-quently, makes the educational discourse unauthentic.